Can mobile phone multimedia messages and text messages improve clinic attendance for Aboriginal children with chronic otitis media? A randomised controlled trial. (25th February 2014) - Phillips, James H; Wigger, Christine; Beissbarth, Jemima; McCallum, Gabrielle B; Leach, Amanda; Morris, Peter S
<x xml:space="preserve">Abstract</x> Aim Does phone multimedia messages (MMS) to families of Indigenous children with tympanic membrane perforation (TMP): (i) increase clinic attendance; (ii) improve ear health; and (iii) provide a culturally appropriate method of health promotion? Methods Fifty‐three Australian Aboriginal children with a TMP living in remote community households with a mobile phone were randomised into intervention (n = 30) and control (n = 23) groups. MMS health messages in local languages were sent to the intervention group over 6 weeks. Results Primary outcome: there was no significant difference in clinic attendance, with 1.3 clinic visits per child in both groups (mean difference −0.1; 95% confidence interval (CI) −1.1, 0.9; P = 0.9). Secondary outcomes: (i) there was no significant change in healed perforation (risk difference 6%; 95% CI −10, 20; P = 0.6), middle ear discharge (risk difference −1%; 95% CI −30, 30; P = 1.0) or perforation size (mean difference 3%; 95% CI −11, 17; P = 0.7) between the groups; (ii) 84% (95% CI 60, 90) in the control and 70% (95% CI 50, 80) in the intervention group were happy to receive MMS health messages in the future. The difference was not significant (risk difference −14%; 95% CI −37, 8; P = 0.3). Conclusions Although there was no improvement in clinic attendance or ear health, this randomised controlled trial of MMS in Indigenous languages demonstrated that MMS is a culturally appropriate form of health promotion. Mobile phones may enhance management of chronic disease in remote and disadvantaged populations.